European elections and their implications for the Cyprus issue: Populist challenges and Turkish Cypriot inclusion - Erol Kaymak (Stiftung Wissenschaft und Politik (SWP), 2024)
One of the big surprises of the June 2024 European Parliamentary elections occurred in the Republic of Cyprus, where a 24-year-old YouTuber and social media influencer, Fidias Panayiotou, won a seat running as an independent having secured over 19 percent of the vote. Whereas the vast majority of polls had predicted the rise of the radical right National People's Front Party (ELAM) in Cyprus along with other far-right parties in Europe, Panayiotou's victory and overall vote tally was unforeseen. His win came at the expense of the left-wing Progressive Party of the Working People (AKEL), dashing the hopes for the re-election of Turkish Cypriot MEP Niyazi Kızılyürek, whose 2019 election to the European Parliament was seen as a milestone for bi-communal relations in divided Cyprus. Kızılyürek's defeat highlights the persistent difficulties in achieving greater political integration and representation for Turkish Cypriots within the EU framework. This underscores the urgent need for inclusive dialogue, economic integration, and proactive measures to address Cyprus's unique challenges, aiming to foster a more cooperative and resilient future for the island. Initiative - in other words, a new model for structured relations with a partner that is very important for the EU and Germany. Here, the EU should also show more flexibility than in the past.
Keywords: 320; European Parliamentary elections 2024; Republic of Cyprus; Democratic Rally (DISY); National People's Front Party (ELAM); Progressive Party of the Working People (AKEL); European People's Party group (EPP); Niyazi Kızılyürek; Annita Demetriou